Pengaruh Kualitas Layanan dan Promosi Social Media terhadap Kepuasan Jemaat dan Loyalitas Jemaat di GBI Aletheia Magelang - Vanessy Soebijantono, Kezia; Santoso, Singgih (STIE Indonesia Banking School, 2025)
Service quality is widely used to assess services provided by either industries, businesses or organizations. However, researchers found a gap in research because the variable was rarely tested in the context of places of worship which is a mass organization that claims service as part of worshiping God. Therefore, researchers intend to study service quality in Christian Churches and its influence on congregational satisfaction and congregational loyalty. Researchers also involved other variables to be tested in this study namely social media promotion, due to the increasingly active use of church social media accounts, especially in conveying information to congregations. Researchers applied quantitative research in the Structural Equation Modelling (SEM) by utilizing the AMOS program to process data. The population in this study were Christians who congregate at GBI Aletheia Magelang. Then, this study used data obtained from 205 respondents selected based on purposive random sampling techniques. The results of the hypothesis test of this study indicate that service quality has a positive and significant effect on congregational satisfaction, social media promotion has a positive and significant effect on congregational satisfaction, and congregational satisfaction has a positive and significant effect on congregational loyalty.